Optical Gain at 637 nm Wavelength in Polymer Waveguide Amplifier Under Commercial LED Pumping for Planar Photonic Integration (Advanced Optical Materials 13/2022). Issue 13 (4th July 2022) - Wang, Ce; Liu, Xin; Zhang, Baoping; Xie, Guohua; Zhou, Zhaoqin; Yang, Xingchen; Ying, Leiying; Mei, Yang; Fan, Wang; Lin, Zhensheng; Zheng, Zhiwei; Zhang, Dan
Abstract : This cover image shows optical amplification at 637 nm that is achieved in polymer waveguides doped with thermally activated delayed fluorescence (TADF) molecules. Under excitation of low‐cost light‐emitting diodes, the molecules realize the process of converting blue‐violet light into red light, which depends on the continuous absorption band of the material and reverse intersystem crossing process. The results, presented by Dan Zhang, Guohua Xie, and co‐workers in article number 2200205, open new avenues for the application of TADF materials in photonic integrated chips.